An empirical study to measure consumer adoption of mobile banking services. (15th December 2021) - Srivastava, Mallika; Fernandes, Semila
In the highly secured and regulated world of banking and financial services and insurance (BFSI), mobile banking (m-banking) has emerged as an innovative technological advancement. The consumer adoption of m-banking technologies has not been measured comprehensively. Through the current study, the authors have made an attempt to measure the consumer adoption of m-banking in developing economy. To support this research, Everett Rogers theory of 'diffusion of innovation' is adopted as theoretical framework. An exploratory study was administered through a structured questionnaire. Non-probabilistic convenience sampling technique was adopted for the study. Confirmatory factor analysis (CFA) was used to establish the measurement model. Additionally, the study also explores the impact of demographic characteristics like gender, age, income, marital status, duration of using smartphones and duration of using internet banking on consumer adoption towards m-banking services using ANOVA.